Phenomenology and the Non-Human Animal
IX, 158 p.
Keywords: The question of the relation between human and non-human animals in theoretical, ethical and political regards has become a prominent topic within the philosophical debates of the last two decades. This volume explores in substantial ways how phenomenology can contribute to these debates. It offers specific insights into the description and interpretation of the experience of the non-human animal, the relation between phenomenology and anthropology, the relation between phenomenology and psychology, as well as ethical considerations.